Importance of Conducting Indoor and Outdoor Events at Secondary Schools in Nepal - Limbu, Chandra Bahadur (Marsyangdi Journal, 2024)
Many secondary schools conduct indoor and outdoor events at schools to improve the holistic development of learners. Both events not only boost academically for students but also improve their self-confidence. The purpose of the study was to find out the importance of conducting indoor and outdoor events in secondary schools and find the strengths behind organizing such events at schools. The research paradigm of this study was positivism, and this quantitative study employed the survey research design to investigate the importance of conducting these events in schools. I selected 75 students and 25 teachers from secondary schools using random sampling for this study. I distributed the questionnaire into two sections to my respondents online, that is, via messenger, to collect the primary data for the study. I used a correlation analysis for the data interpretation of the collected from this study. I divided the responses received into students’ responses and teachers’ responses. The findings of the students’ response revealed that a fixed schedule for extracurricular activities, trained and experienced coordinators, and enough materials for the events are essential to conduct indoor and outdoor events in schools. The findings of the teachers’ responses show that extracurricular activities improve the academic performance of students developing different language skills. The findings of this study have implications for school administrators, teachers, parents, students, and textbook writers.